2000
DOI: 10.1097/00007890-200006150-00021
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Deposition in the Globus Pallidus in Patients With Biliary Atresia

Abstract: Manganese accumulates in the brain during cholestasis associated with biliary atresia and disappears after hepatic transplantation. Manganese deposition is likely to be subclinical and reversible but may be associated with some age-related neurologic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 29 publications
1
27
0
2
Order By: Relevance
“…AHD may accompany any form of chronic liver disease associated with portosystemic shunting and has been described in the setting of viral hepatitis, alcoholic cirrhosis, alpha-1 antitrypsin deficiency, nonalcoholic steatohepatitis, autoimmune hepatitis, primary and secondary biliary cirrhosis [67,114], biliary atresia [51], Byler's disease [108] and cryptogenic forms of cirrhosis [8]. Occasionally, AHD occurs in patients who have portosystemic shunts without underlying hepatocellular disease, such as those with hereditary hemorrhagic telangiectasias, surgeries or portal vein thrombosis [9,30,93,100,127,144,164].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…AHD may accompany any form of chronic liver disease associated with portosystemic shunting and has been described in the setting of viral hepatitis, alcoholic cirrhosis, alpha-1 antitrypsin deficiency, nonalcoholic steatohepatitis, autoimmune hepatitis, primary and secondary biliary cirrhosis [67,114], biliary atresia [51], Byler's disease [108] and cryptogenic forms of cirrhosis [8]. Occasionally, AHD occurs in patients who have portosystemic shunts without underlying hepatocellular disease, such as those with hereditary hemorrhagic telangiectasias, surgeries or portal vein thrombosis [9,30,93,100,127,144,164].…”
Section: Pathogenesismentioning
confidence: 99%
“…Symptoms of AHD usually begin in adulthood, often in the fifth to sixth decade of life [8, 67,114,154]; however, AHD occasionally affects children [51,108], so the age at onset alone cannot distinguish AHD from Wilson disease (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…There is post-mortem evidence for manganese accumulation within the globus pallidus in patients dying with established cirrhosis. 13 14 Furthermore, marked hyperintensity of the globus pallidus (GP) on T 1 weighted magnetic resonance imaging (MRI) has been reported both in patients with cirrhosis 13 15-19 and in patients with hypermanganesaemia due to occupational exposure, 20 biliary atresia, 21 and total parenteral nutrition. 22 We hypothesised that the fatigue experienced by patients with PBC, in the absence of cirrhosis, may occur as a consequence of increased GP manganese concentrations as a result of impaired biliary excretion.…”
mentioning
confidence: 99%
“…4,10,11 Extrapyramidal symptoms may result from a toxic effect of manganese on basal ganglia dopaminergic functions. 12 Spahr and colleagues 1 have reported that there was no significant correlation between blood manganese levels and extrapyramidal symptoms. In our patient, although the blood manganese level was elevated significantly, he only presented with flapping tremor without any other signs of extrapyramidal dysfunction.…”
Section: Discussionmentioning
confidence: 98%